Optimization of Electronic Control System Learning through Op-Amp Trainer Implementation - Resa Pramudita; Ibrohim Ibrohim; Yoyo Somantri; Muhammad Adli Rizqulloh; Roer Eka Pawinanto; Maman Somantri (PTE FTK UIN Ar-Raniry, 2023)
This research aims to determine the effectiveness of the implementation of Op-Amp trainer in the learning of electronic control systems on the learning outcomes of students in the cognitive and psychomotor domains. The research was conducted using a quasi-experiment method and a sample of 32 students from the experimental and control classes. Data analysis was conducted using hypothesis testing and N-Gain. The results showed that the average learning outcomes of students in both the cognitive and psychomotor domains are good and there was a significant difference in learning outcomes with the experimental class higher. The conclusion of this research is that the implementation of Op-Amp trainer in the learning of electronic control systems is effective in improving student learning outcomes in the cognitive and psychomotor domains when compared to simulation-based learning media.